The Circumstances of the Development of Diplomacy and the Rules Governing it - Guesmia, Mohamed (Journal of Legal Studies and Researches, 2021)
The aim of the study is to know diplomacy as a phenomenon, and the conditions for its development before the codification of international diplomatic law under the International Convention on Diplomatic Relations of 1961, especially if we know that the most important sources of this law is international custom. It was concluded that the international community was compelled to regulate international relations and the rules that govern them, and this is due to the rules governing diplomatic representation, where the aforementioned agreement was introduced despite previous attempts to regulate these relations.